Multistakeholder scientific advice for medicinal products used in combination with a medical device or a companion diagnostic in the EU—summary of a Focus group discussion - Aarum, Stiina; Popp, Claudia; Hunter, Alexa; Skvarc, Miha; Reischl, Ilona; Zander, Hilke; Zinserling, Joerg; van Leeuwen, Petra; Sutch, Jonathan; Chesworth, Tim; Kapeller, Elisabeth; Emmendoerffer, Andreas; et al. (Frontiers in Medicine, 2025)
Although there is growing use of medicinal products in combination with medical devices, including in vitro diagnostics (IVDs) and software as a medical device, their development in the EU is proving to be more challenging due to the complexities in working across the regulatory frameworks for medicinal products, medical devices and IVDs. One of the concerns is the lack of a multistakeholder platform [European Medicines Agency (EMA)/Scientific Advice Working Party (SAWP); National Competent Authorities (NCAs) in charge of medicinal products; NCAs for medical devices; notified bodies (NBs)] for scientific and regulatory advice on medicinal products used in combination with medical devices or IVDs [including companion diagnostics (CDx)]. A multistakeholder platform would allow for an opportunity to discuss the scientific expectations of the different decision makers involved and guide the identification of an appropriate development path for both medicine and medical device/IVD (including CDx). In search of a pragmatic approach to facilitate discussions on evidence generation plans, it was agreed in the “9th EMA-Industry stakeholder platform on research and development support” meeting in December 2022 to set up a dedicated Focus group to determine the possibility of provision of scientific advice for medicinal products in combination with a medical device or IVD (including CDx). The Focus group had participants from the EMA SAWP, the NCAs, the NBs, and industry and the EMA. The group explored what kind of scientific questions would benefit from being addressed in comprehensive discussions on evidence generation planning in a multistakeholder setting, and who would be the required decision makers and experts for such multidisciplinary discussions. The discussions covered nine study cases: four were drug-device combinations and five were drug—IVD/CDx combinations. The scope of the discussions excluded stand-alone high-risk medical devices and IVDs for which there was an ongoing scientific advice pilot involving the medical device expert panels. In addition, low-risk stand-alone medical device/IVD developments were also out-of-scope. This article presents the insights of the discussions on the nine study cases reviewed by the Focus group and explores options for next steps to inform future policy and technical discussions on these innovative healthcare developments.